2021
DOI: 10.1007/s00405-021-07183-9
|View full text |Cite
|
Sign up to set email alerts
|

The effect of virtual reality on temporal bone anatomy evaluation and performance

Abstract: Purpose There is only limited data on the application of virtual reality (VR) for the evaluation of temporal bone anatomy. The aim of the present study was to compare the VR environment to traditional cross-sectional viewing of computed tomography images in a simulated preoperative planning setting in novice and expert surgeons. Methods A novice (n = 5) and an expert group (n = 5), based on their otosurgery experience, were created. The participants were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…The inadequate positioning of the HMD and eyeline (e.g., HMD straps were too loose) or possible eye disorders may have been the basis for these reports although the quality of HRCT image data in our VR setup was evaluated by experienced otosurgeons prior to the course. Despite these shortcomings, the participants positively evaluated VR training and planning during the course, which was in line with previous research (Timonen et al, 2021(Timonen et al, , 2020.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The inadequate positioning of the HMD and eyeline (e.g., HMD straps were too loose) or possible eye disorders may have been the basis for these reports although the quality of HRCT image data in our VR setup was evaluated by experienced otosurgeons prior to the course. Despite these shortcomings, the participants positively evaluated VR training and planning during the course, which was in line with previous research (Timonen et al, 2021(Timonen et al, , 2020.…”
Section: Discussionsupporting
confidence: 85%
“…Unfortunately, interpretation of a radiological image or training in preoperative planning is not commonly implemented in trainee-level temporal bone dissection courses. Previous studies have shown that VR planning and simulation may offer a feasible method to enhance the student's understanding of the anatomy of the temporal bone and provide more effective training for novice surgeons and trainees (Al-Noury, 2012;Locketz et al, 2017;Timonen et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative and quantitative outcomes reported by included studies are listed according to the learning determinant category. Results from these studies are summarized in “Statistical results” if they are supported by statistical analysis, or “Non-statistical results” if they are not Possible learning determinants count, n (%) Qualitative outcome measures Quantitative outcome measures Statistical results Non-statistical results Student perceptions 212121 (84) - Usefulness or efficiency for anatomy learning [ 21 , 22 , 35 37 , 39 , 42 44 , 46 , 48 , 49 , 54 , 55 ] - Enjoyment [ 21 , 22 , 32 , 35 , 42 , 43 , 46 , 49 , 52 ] - Ease of use [ 22 , 32 , 35 , 39 , 42 44 , 46 ] - Motivation [ 32 , 45 , 48 , 55 ] - Instructional Materials Motivation Survey [ 48 ] - Engagement or interest [ 45 , 48 – 50 ] - Ease of understanding [ 22 , 32 , 45 , 51 , 52 ] - Value - Revised Motivated Strategies for Learning Questionnaire [ 55 ] - Preferen...…”
Section: Resultsmentioning
confidence: 99%
“…- Usefulness or efficiency for anatomy learning [ 21 , 22 , 35 37 , 39 , 42 44 , 46 , 48 , 49 , 54 , 55 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation